APLIKASI TEPUNG DAUN KAYU MANIS SEBAGAI SUPLEMEN PAKAN TERHADAP KUALITAS DAGING UDANG VANAME (Litopenaeus vannamei): Application of Cinnamon Leaf Flour as Feed Supplement to Meat Quality of Vannamei Shrimp (Litopenaeus vannamei) - Neny Mariyani; Andri Hendriana (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2020)
This study aims to apply the appication of cinnamon leaf flour in feeding to the meat quality of vannamei shrimp (Litopenaeus vannamei). The concentrations of cinnamon leaf flour given were 0%, 0,5%, 1,0% and 1,5%. The vannamei shrimp used had an average weight of 10,06 ± 0,15 g/tail which was kept in an aquarium for 60 days. The quality test result showed that on 1,5% treatment, the shrimp meat had the lowest fat content on 1,46% and the highest HDL content on 96,75%. The results of organoleptic test on the quality of shrimp meat showed no difference in aroma, color, taste and texture that could be detected by the panelists (p>0,05). The average responses were: aroma 4,43, 4,31, 4,45; color 4,67, 4,67, 4,60; texture 4,52, 4,67, 4,52 and taste 4,48, 4,38, 4,52. From the results of the organoleptic test, all parameters showed a number above 4, where the value of 4 indicated that tested parameters were as good as the control (0%).